The natural sciences : a student's guide - Bloom, John A., 1952- (Wheaton, Illinois : Crossway, 2015)
In this accessible guide for students, a well-regarded science professor introduces readers to the natural sciences from a distinctly Christian perspective. Starting with the classical view of God as the Creator and Sustainer of the universe, this book lays the biblical foundation for the study of the natural world and explores the history of scientific reflection since Aristotle. Bloom argues that the Christian worldview provides the best grounds for scientific investigation, offering readers the framework they need to think and speak clearly about the pursuit of scientific knowledge. - Publisher.
What is the Christian intellectual tradition in the sciences? -- Early science: the handmaiden to theology -- The rift of the enlightenment -- The wrong road: science as methodological naturalism -- Barricades: the end of the road for reason and experience -- The way home: thinking outside the box of naturalism -- Questions for reflection -- Timeline?
Includes bibliographical references and index.
Keywords: Religion and science; Christian philosophy; Naturalism -- Religious aspects -- Christianity; Science -- Philosophy